2022
DOI: 10.25077/jagur.4.1.8-17.2022
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: One of the factors hindering the development of upland rice cultivation among annual crops is the limited number of shade-tolerant upland rice varieties. It is very important to assemble shade-tolerant upland rice varieties with high yields. The purpose of the study was to determine the effect of shade on the growth and productivity of five genotypes of upland rice. This research was carried out in the experimental garden of the Faculty of Agriculture, the Islamic University of North Sumatra with an altitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The application of various doses of inorganic fertilizers did not have a significant effect on the aging of panicle shoots and harvesting age, but the results showed that Uva Buya cultivars aged relatively faster than Pae bohe and Buncaili cultivars. This is because the Uva Buya cultivar has the characteristics of a panicle outage and a faster harvest age compared to the Pae bohe and Buncaili cultivars, (Hariyati and Sabarudin, 2021;Chaniago, et al, 2022;Tiwari, et al, 20…”
Section: Discussionmentioning
confidence: 99%
“…The application of various doses of inorganic fertilizers did not have a significant effect on the aging of panicle shoots and harvesting age, but the results showed that Uva Buya cultivars aged relatively faster than Pae bohe and Buncaili cultivars. This is because the Uva Buya cultivar has the characteristics of a panicle outage and a faster harvest age compared to the Pae bohe and Buncaili cultivars, (Hariyati and Sabarudin, 2021;Chaniago, et al, 2022;Tiwari, et al, 20…”
Section: Discussionmentioning
confidence: 99%
“…Availability of nutrients that can absorbed by plants is one possible factor influences level production and growth of plants, so if the required nutrients for growth are fulfilled, plants will obtain optimal production as well quality [22]. Precise concentrations could supports metabolic processes in plants and have a good influence on growth and production [23].…”
Section: Plant Fresh Weightmentioning
confidence: 99%
“…Kelimpahan biji gulma tersebut dipengaruhi berbagai faktor seperti pengelolaan lahan (Cabrera-Pérez et al, 2022;Pinke et al, 2022;Rahman et al, 2012) dan aplikasi herbisida dalam praksis budidaya tanaman (Comeau & Fraser, 2018;Deligios et al, 2019;Gazola et al, 2022;Idziak & Woznica, 2020). Perubahan komposisi gulma yang tumbuh juga dipengaruhi oleh cara olah tanah (Chaniago et al, 2023). Komposisi dan dominansi gulma akan menentukan rekomendasi pengendalian yang diterapkan dan teknik pengendalian yang dipilih harus tetap memperhatikan dampak minimal terhadap lingkungan (Antralina et al, 2014).…”
Section: Dominansi Gulmaunclassified